ҚАЗАҚСТАН РЕСПУБЛИКАСЫ КӘСІПОРЫНДАРЫНА САПА МЕНЕДЖМЕНТІ ЖҮЙЕЛЕРІН ЕНГІЗУ. (Journal of Economic Research & Business Administration, 2016)
This article describes the Quality Management System: ISO 9000. The ways of implementing the Quality Management System in the Republic of Kazakhstan enterprises.